TICs: A key element of communication among university faculty - Tomàs Folch, Marina; Segovia Tamayo, Paola (Education Policy Analysis Archives, 2008)
This article exposes the interest that the technologies of information and communication (TICs) present in the development of the universities, especially, in the development of its processes of information management and internal communication. Based on a review of the state of the art in this field, different theoretical approaches from the field of theory of communication and institutional communication are discussed, allowing us to visualize the crucial role that information management has in the processes of modernization of the university. Finally, a methodological design for the study of the role of the TICs in information management in the university institution is presented, specifically in relation to the influence that the widespread use of the TICs has had on communication among university faculty.